- Shifts up 5 units.
A.
B.
C.
D.
Answer:
A, g(x) = 7x + 5
Step-by-step explanation:
applying these translations to the parent function f(x) = x, we would get the following equation:
g(x) = 7x + 5
a vertical compression is written before the parent function (in this case f(x)=x), and a shift up is written next to the function. both of these are without parentheses
the answer would be A, g(x) = 7x + 5
9y = 2
- 4x +y = -35
Answer:
Step-by-step explanation:
9y=2
-4x+y=-35
____________
-4x=-y-35
-4x+35=-y
4x-35=y
____________
9(4x-35)=2
36x- 315=2
36x=317
x=8.8055555555555555555555555555555555 you get the idea
Answer: The prove is mentioned below.
Step-by-step explanation:
Here the given functions are,
We have to prove that: f(g(x)) = x and g(f(x)) = x.
Since
⇒
⇒
⇒
Now,
⇒
⇒
⇒
Answer with Step-by-step explanation:
We are given that
We have to confirm that f and g are inverses by showing that f(g(x))=x=g(f(x))
Hence, f(g(x))=g(f(x))=x
Therefore, f and g are inverses.
81y4 – 16x2, the difference of squares
81y4 – 72xy2 – 16x2, a perfect square trinomial
81y4 – 72xy2 – 16x216, the difference of squares
Consider the expression You can see that in both brackets are the same terms and , but signs are different. So you can use formula for the difference of squares:
According to this formula,
Answer: correct choice is B.